Negatively charged ions to probe self-assembled monolayer reorganization driven by interchain interactions. Issue 33 (6th August 2021) - Tricase, Angelo; Stefanachi, Angela; Picca, Rosaria Anna; Macchia, Eleonora; Favia, Alessandro; Leonetti, Francesco; Scamarcio, Gaetano; Blasi, Davide; Bollella, Paolo; Torsi, Luisa
Abstract : The kinetics and the diffusional/interpenetration data of the probing species over time as well as the spectroscopic data provide key information on the interchain reorganization in an electric field. Abstract : A combined cyclic voltammetry (CV) and grazing angle attenuated total reflectance (GA-ATR) IR study on the interchain interaction driven reorganization of self-assembled monolayers (SAMs) in an electric field was presented. The study focused on an N -(2-hydroxyethyl)-3-mercaptopropanamide (NMPA) SAM endowed with interchain hydrogen bonding, strongly affected by an external electric field interacting with the dipole moment associated with the hydrogen bonding. Conversely, a 1-hexanethiol SAM was characterized by interchain hydrophobic interaction not affected by the applied field. These features were demonstrated by means of reiterated CV experiments involving an electroactive negatively charged probe, namely Fe(CN)6 4−, and a Au-SAM serving as a working electrode. The diffusional/interpenetration and kinetics parameters provided the apparent electron transfer rate constant ( k 0 ) values. For the NMPA, the interchain rearrangement kinetics was that of an ion-permeable layer that reached, in the electric field, a steady-state configuration after about 50 minutes. The 1-hexanethiol chains' reorganization exhibited more complex kinetics involving a first phase ( ca. 50 minutes) of an ion-permeable phase followed by a sharp decrease in the anodic peak current related to the tightening of the structure, likely due to the interchain hydrophobic interaction, hindering ion diffusion. The change in the SAM structure upon cycling in the electric field was confirmed by the GA-ATR measurements.